2009
DOI: 10.1515/jpm.2009.046
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin induced placental cell apoptosis could be mediated via the ADIPOR1-receptor in pre-eclampsia with IUGR

Abstract: The activity of placental adipocytokines and their receptor genes in severe PE may suggest an important role in placental angiogenesis. Placental apoptosis induced by adiponectin could be mediated via the ADIPOR1-receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
11
0
3
Order By: Relevance
“…Also Yang et al reported the ability of adiponectin to promote endothelial differentiation in peripheral blood CD14þ monocytes, by inducing morphology changes and upregulating EC markers [76]. On the contrary, in other studies it has been reported an ''anti-endothelial action'' for the adipokine, which was shown to increases the caspase-mediated apoptosis in endothelial cells [77,78]. To our knowledge, no studies describe the effect of adiponectin on blood vessels of chorionic villi.…”
Section: Adipokines and Placentamentioning
confidence: 94%
“…Also Yang et al reported the ability of adiponectin to promote endothelial differentiation in peripheral blood CD14þ monocytes, by inducing morphology changes and upregulating EC markers [76]. On the contrary, in other studies it has been reported an ''anti-endothelial action'' for the adipokine, which was shown to increases the caspase-mediated apoptosis in endothelial cells [77,78]. To our knowledge, no studies describe the effect of adiponectin on blood vessels of chorionic villi.…”
Section: Adipokines and Placentamentioning
confidence: 94%
“…Leptin also affects the expression of several genes involved in angiogenesis such as matrix metalloproteinase (MMP)-2 and -9 (Cao et al, 2001). Leptin was implicated in the pathogenesis of several diseases, including essential hypertension and preeclampsia; recently, several groups reported increased serum and placental leptin levels in preeclamptic patients (Jarvenpaa et al, 2009). However, it is unknown whether elevated leptin levels are the causes or consequences of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…проде-монстрировали способность адипонектина усиливать дифференциацию эндотелиальных клеток пупочной вены человека и способствовать ангиогенезу [40]. Другие исследования показали противоположное, «антиэндотелиальное действие» адипонектина, где по-следний увеличивал каспазоопосредованный апоптоз в клетках эндотелия [41].…”
Section: роль адипонектина во время беременностиunclassified